Assistance for Youth Counselors in Efforts to Improve the Implementation of PIK-R - Nuzliati T. Djama; Sahnawi Marsaoly (Universitas Pendidikan Ganesha, 2023)
The Youth Information and Counseling Center is a forum for program activities managed for teenagers. The aim of this service is to provide refreshing insight into the function of PIK teenagers as a youth information center and to provide knowledge and skills to youth counselors regarding adolescent reproductive health. This is done by optimizing PIK-KR recording and reporting and training youth counselors by means of socialization through role playing, lectures, discussions and mentoring on the PIK-R program as well as structuring the reporting recording system and simulating how to fill out PIK-R documents. Testing the knowledge and skills of adolescent cadres is regarding adolescent reproductive health and its problems by providing pre-tests and post-tests. The results of the community service show that out of 30 training participants in the pre-test, 28 people got a score <50 and 2 participants got a score >50, with an average score of 40.8. After the intervention was carried out, there was an increase in knowledge as evidenced by an increase in the post-test scores of the training participants. The results showed an increase with an average score of 80. The conclusion of this community service is that the intervention carried out by the community service team has proven to be effective in increasing the knowledge of training participants. It is recommended to continue the same intervention with other trainees to improve their overall knowledge.